A construção de conhecimentos sobre os processos erosivos urbanos na geografia escolar - Oliveira, Amanda Satil de (2024)
The scenario of constant and growing urbanization brings with it several issues, ysical-natural components of the geographic space, as it results from the interaction between soil, relief, climate, geology, water, among others, as well as the such as erosive processes. To understand such processes, we consider the ph social relations established in the way society appropriates geographic space. Based on this framework, our general objective is to understand how knowledge related to urban erosive processes has been addressed in School Geography and its importance for the critical formation of students. Specific objectives include identifying how theoretical-methodological knowledge on Geography teaching, physical-natural components, and erosive processes are being discussed in scientific and academic production; investigating how knowledge about erosive processes is proposed in the National Common Curricular Base (BNCC), the Curricular Document for Goiás (DCGO), and the Geography textbooks for 6th grade of Elementary School; and analyzing the theoretical- methodological knowledge mobilized by Geography teachers for building learning about erosive processes in Basic Education and, from this, propose teaching methodologies to address the topic in Geography lessons. To achieve these objectives, we chose a qualitative research methodology. As methodological procedures, we conducted a literature review, State of Knowledge analysis, textbook analysis, and document analysis of the BNCC and DCGO, along with the application of questionnaires and classroom observations. The bibliographic survey was carried out in books, articles, theses, and dissertations. The State of Knowledge was carried out on the CAPES platform and Google Scholar with the aim of identifying, selecting, and analyzing works that could contribute to the development of the research. The documentary analysis of the BNCC and DCGO aimed to identify how erosive processes are addressed in the 6th grade, final years of Elementary School, the phase in which the curriculum proposes work on these processes based on their correlation with the physical-natural components of geographic space. The questionnaire was applied to four teachers, two from the municipal network of Goiânia and two from the state network of Goiás, based in Goiânia. Classroom observations aimed to understand how this content has been taught in School Geography. Regarding the textbooks, we conclude that some collections have made more significant progress in integrating the physical- natural components of geographic space with society. In the curricula, we found that urban erosive processes have not received the due attention. This study allowed us to understand that the city of Goiânia (GO) is a setting for erosive processes and floods. In this sense, studying the risks of this phenomenon from Basic Education represents a possibility of mitigating social inequalities through student awareness and the formation of reflective subjects about their realities.